A process for producing a low-tumor low-roughness super-thick copper foil by electrolysis

CN122918655APending Publication Date: 2026-10-16HENGTONG PRECISION COPPER FOIL TECHNOLOGY (DEYANG) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611056077.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-16
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]此外,现阶段行业通常采用生箔后粗化、固化、合金化等表面处理工艺改善铜箔表面性能、提升基材结合力,但该类后续处理手段仅能优化表层状态,无法根除电解沉积阶段产生的本体铜瘤缺陷

Benefits of technology

本发明所述的电解生箔工艺基于硫酸铜电解液体系,引入包含整平剂、光亮剂、抑制剂与表面活性剂的复合型添加剂体系,依靠多组分添加剂协同调控阴极辊界面铜离子电结晶行为,从电解沉积源头抑制铜离子异常枝晶析出与铜瘤形核生长,精细化调控铜箔微观表面形貌,无需依靠生箔后粗化、固化等表面处理工序弥补原生本体缺陷,同时适配超厚铜箔长时高负荷电沉积工况匹配专属电解工艺参数,在目标厚度区间内稳定赋予铜箔优异的综合力学性能,成品可满足高频高速覆铜板、大电流承载PCB、新能源汽车电池连接片等高端应用场景对超厚铜箔低粗糙度、高使用可靠性的严苛需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918655A_ABST
    Figure CN122918655A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of low copper tumor low roughness's ultra-thick copper foil electrolytic foil process, belong to copper foil technical field.The ultra-thick copper foil electrolytic foil process of the present application includes the following steps: S1, copper source, sulfuric acid, chlorine source, leveling agent, brightener, inhibitor and surfactant are added to water and stirred uniformly, to obtain electrolyte;S2, cathode roller and anode are immersed in electroplating solution and electrolytic deposition is carried out, to obtain low copper tumor low roughness's ultra-thick copper foil.Based on copper sulfate system electrolyte, leveling agent, brightener, inhibitor, surfactant multi-component additive concentration is compounded and strictly controlled, rely on the synergistic effect of each additive to regulate and control cathode interface copper ion electric crystallization process, inhibit copper ion abnormal dendrite precipitation from electrolytic deposition source, one-step preparation with low copper tumor, low roughness characteristics of ultra-thick foil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of copper foil technology, and particularly relates to an electrolytic foil production process for ultra-thick copper foil with low copper nodules and low roughness. Background Technology

[0002] With the rapid iteration and upgrading of high-end electronic industries such as new energy vehicles, 5G communications, AI servers, and high-power power modules, high power, high current, and high frequency have become the core development trends of electronic devices. The market demand for printed circuit boards (PCBs) capable of carrying high currents is experiencing explosive growth. In the application scenarios of high-power electronic devices, copper foil of ordinary thickness can no longer meet the core performance requirements of high current carrying capacity and high heat dissipation. Ultra-thick copper foil with a thickness of ≥100μm, with its excellent current carrying capacity and heat dissipation performance, has become a core key material for the preparation of high-current PCBs, power battery connectors, busbars, and high-frequency power modules, and has irreplaceable application value in the field of high-end electronic manufacturing.

[0003] Ultra-thick copper foil is mainly produced using an electrolytic foil-forming process. However, compared to the conventional 35μm standard copper foil, the electroplating deposition time for ultra-thick copper foil is significantly increased by 3-6 times. The characteristics of this long-duration electrodeposition process lead to stringent challenges in surface quality control during its production. During the long-term electrocrystallization process on the cathode roller, copper ions are prone to abnormal growth, resulting in numerous hemispherical or dendritic copper nodules on the copper foil surface. These nodules can reach a height of 5μm-20μm, directly causing a deterioration in the surface roughness of the copper foil. The Rz value generally exceeds the acceptable range of 5μm-8μm, becoming a core bottleneck restricting the improvement of the quality of ultra-thick copper foil.

[0004] Copper nodules on the surface of copper foil can lead to multiple technical problems, seriously affecting the reliability of ultra-thick copper foil in high-end high-power devices. First, protruding copper nodules can cause insufficient lamination between the copper foil and the resin substrate, easily forming voids and significantly reducing the peel strength between the copper foil and the substrate, resulting in a significant decrease in lamination adhesion. Second, the uneven surface caused by copper nodules can lead to uneven etching processes, resulting in rough and inaccurate circuit edges, which can damage the integrity of high-frequency signal transmission. At the same time, in high-voltage and high-power operating scenarios, sharp copper nodule structures can cause local electric field concentration, greatly increasing the safety risks of insulation failure and partial discharge. In addition, the area covered by copper nodules may experience coarsening and insufficient subsequent surface treatment, directly deteriorating the oxidation resistance and solderability of the copper foil.

[0005] Currently, most mature copper foil additive systems in the industry are designed for copper foils with standard thicknesses of 12μm-70μm. The mainstream chloride ion + polyethylene glycol (PEG) + sodium 3-mercapto-1-propanesulfonate (MPS) composite system is unsuitable for the long-term, high-load electrodeposition conditions of ultra-thick copper foils. During the production of ultra-thick copper foils, the prolonged high current density environment causes rapid decomposition of PEG additives, significantly reducing their original leveling efficiency; simultaneously, the consumption rate of MPS brightener accelerates dramatically, and its concentration fluctuations cannot stably inhibit copper nodule growth. In addition, the significantly increased electrolyte convection intensity during ultra-thick deposition completely disrupts the stable adsorption balance of additives on the cathode surface, further exacerbating the copper nodule growth problem.

[0006] Furthermore, the industry currently employs surface treatment processes such as roughening, curing, and alloying after foil production to improve the surface properties of copper foil and enhance substrate adhesion. However, these subsequent treatments can only optimize the surface condition and cannot eliminate the bulk copper nodules generated during the electrolytic deposition stage. For ultra-thick copper foils with excessively large copper nodules and excessive bulk roughness, subsequent surface treatments not only fail to compensate for the original defects but may also further exacerbate surface flatness deviations.

[0007] Therefore, there is an urgent need to develop an electrolytic foil production process suitable for the preparation of ultra-thick copper foil. This process can suppress the formation of copper nodules and precisely control the surface roughness of copper foil in the source electrolytic deposition process, thereby matching the high-quality and high-reliability requirements of high-end high-power electronic devices for ultra-thick copper foil. Summary of the Invention

[0008] To address the aforementioned technical problems, this invention provides an electrolytic greening process for ultra-thick copper foil with low copper nodules and low roughness. Based on a copper sulfate electrolyte system, a multi-component additive system of leveling agents, brighteners, inhibitors, and surfactants is formulated and its concentration is strictly controlled. The process relies on the synergistic effect of these additives to regulate the electrocrystallization process of copper ions at the cathode interface, thereby inhibiting the abnormal dendrite precipitation of copper ions from the source of electrolytic deposition and preparing ultra-thick green foil with both low copper nodules and low roughness in one step.

[0009] The first objective of this invention is to provide a process for electrolytically producing ultra-thick copper foil with low copper nodules and low roughness, comprising the following steps: S1. Add copper source, sulfuric acid, chlorine source, leveling agent, brightener, inhibitor and surfactant to water and stir evenly to obtain electrolyte; S2. Immerse the cathode roller and anode in the electroplating solution for electrolytic deposition to obtain the ultra-thick copper foil with low copper nodules and low roughness.

[0010] In one embodiment of the present invention, in S1, the temperature of the water is 48°C-54°C; this temperature range can take into account both the copper ion electrodeposition rate and the stability of various additives in the system, avoiding the problems of low deposition rate at low temperature and rapid decomposition and failure of additives caused by high temperature.

[0011] In one embodiment of the present invention, in S1, the copper source is copper sulfate; And / or, the chlorine source is selected from hydrochloric acid and / or sodium chloride; the chloride ions in the chlorine source can act as a synergistic adsorption promoter of the brightener, and help regulate the electrocrystallization behavior of copper ions at the cathode interface; And / or, the leveling agent is polyethylene glycol (PEG); its polymer chains can selectively adsorb on the raised areas of the copper foil surface, increase the polarization resistance of the raised areas, inhibit the preferential deposition of copper ions at the raised areas, and promote preferential electrodeposition in the recessed areas to achieve micro-leveling. At the same time, it can work with chloride ions in the system to form a dynamic adsorption barrier film at the cathode interface, and precisely control the diffusion path of copper ions. And / or, the brightener is sodium 3-mercapto-1-propanesulfonate (MPS); the brightener can rely on the intramolecular thiol group to form a strong adsorption effect with the copper foil surface, which promotes the reduction of copper ions to adsorbed atoms before deposition, effectively increasing the crystal nucleus generation density to refine the grains and inhibit the growth of dendrites and copper nodules; chloride ions in the system can synergistically accelerate the reduction kinetics of copper ions, while the leveling agent will generate a steric hindrance effect, which restricts the brightener to play an efficient deposition role only in the micro-recessed areas of the copper foil, so as to achieve uniform electrocrystallization on the copper foil surface; And / or, the inhibitor is polypropylene glycol (PPG); its polyether chain can be specifically adsorbed at the active site of copper cysts with high curvature on copper foil and form a dense barrier layer. By blocking the three-dimensional nucleation process of copper ions at this site, it inhibits the nucleation of copper cysts from the source, slows down the continuous growth rate of copper cysts, and effectively limits the growth of three-dimensional protrusions of copper cysts. And / or, the surfactant is selected from sodium dodecyl sulfate (SDS) and / or hexadecyltrimethylammonium bromide (CTAB); such surfactants can reduce the surface tension of the electrolyte, promote the uniform dispersion of various additives, avoid local concentration fluctuations, stabilize the micelle structure of the additives, improve the overall dispersion stability of the additives, and prevent the additives from agglomerating and decomposing under long-term electrolysis conditions.

[0012] In one embodiment of the present invention, in S1, the concentration of the copper source in the electrolyte is 290 g / L-310 g / L, the concentration of sulfuric acid is 90 g / L-120 g / L, the concentration of the chlorine source is 30 mg / L-60 mg / L, the concentration of the leveling agent is 13 mg / L-30 mg / L, the concentration of the brightener is 1.0 mg / L-3.0 mg / L, the concentration of the inhibitor is 7 mg / L-20 mg / L, and the concentration of the surfactant is 1.0 mg / L-3.5 mg / L. The system uses a high-concentration copper source-sulfuric acid electrolyte, and sufficient copper ions can meet the ion supply requirements during the rapid deposition process of ultra-thick copper foil.

[0013] In one embodiment of the present invention, in S2, the cathode roller is made of titanium / stainless steel.

[0014] In one embodiment of the present invention, in S2, the surface roughness of the cathode roller does not exceed 2 μm; the low roughness of the roller surface can reduce the active sites for nucleation on the roller surface, reduce the abnormal crystallization precipitation of copper ions from the source, and inhibit the formation of copper nodules.

[0015] In one embodiment of the present invention, in S2, the anode material is an iridium-coated titanium plate.

[0016] In one embodiment of the present invention, in S2, during the electrolytic deposition process, the distance between the cathode roller and the anode is 20mm-30mm.

[0017] In one embodiment of the present invention, in S2, the current density of the electrolytic deposition is 12 A / dm³. 2 -18A / dm 2 The foil production line speed is 1m / min-2m / min; the two parameters are matched to ensure that the overall thickness of the ultra-thick copper foil is uniform.

[0018] In one embodiment of the present invention, in S2, the ultra-thick copper foil with low copper nodules and low roughness has a thickness of 100μm-210μm, a surface roughness of ≤1.7μm, a copper nodule height of ≤1.6μm, a tensile strength of ≥350MPa, and an elongation of ≥20%.

[0019] The technical solution of the present invention has the following advantages compared with the prior art: The electrolytic foil-forming process described in this invention is based on a copper sulfate electrolyte system and introduces a composite additive system containing leveling agents, brighteners, inhibitors, and surfactants. By relying on the synergistic regulation of multi-component additives to control the electrocrystallization behavior of copper ions at the cathode roller interface, it inhibits abnormal dendrite precipitation and copper nodule nucleation growth of copper ions from the source of electrolytic deposition. It precisely controls the microscopic surface morphology of the copper foil, eliminating the need for surface treatment processes such as roughening and curing after foil formation to compensate for original defects. At the same time, it is adapted to the long-term, high-load electrodeposition conditions of ultra-thick copper foil and matches exclusive electrolytic process parameters. Within the target thickness range, it stably imparts excellent comprehensive mechanical properties to the copper foil. The finished product can meet the stringent requirements of high-frequency and high-speed copper-clad laminates, high-current PCBs, and new energy vehicle battery connectors for ultra-thick copper foil with low roughness and high reliability. Attached Figure Description

[0020] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings, wherein: Figure 1 Here is a surface SEM image of the ultra-thick copper foil prepared in Example 1 of this invention; Figure 2 Here is a surface SEM image of the ultra-thick copper foil prepared in Comparative Example 1 of this invention; Figure 3 The image shows the surface metallographic structure of the ultra-thick copper foil prepared in Example 1 of this invention. Figure 4 The image shows the surface metallographic structure of the ultra-thick copper foil prepared in Example 2 of this invention. Figure 5 The image shows the surface metallographic structure of the ultra-thick copper foil prepared in Example 3 of this invention. Figure 6 This is a cross-sectional metallographic image of the ultra-thick copper foil prepared in Comparative Example 1 of the present invention. Detailed Implementation

[0021] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.

[0022] In this invention, unless otherwise stated, the polyethylene glycol (PEG) used in the examples is PEG-4000, purchased from Wuhan Jihechang New Material Co., Ltd.

[0023] In this invention, unless otherwise stated, the polypropylene glycol (PPG) used in the examples is PPG-1000, purchased from Wuhan Jihechang New Material Co., Ltd.

[0024] In this invention, unless otherwise stated, the maximum allowable current of the cathode roller used in the embodiments is 60kA, the diameter is 1380mm, and its surface is mirror polished with a surface roughness of 2.0μm. Example 1

[0025] The low-copper-nodule, low-roughness ultra-thick copper foil electrolytic foil production process of this embodiment specifically includes the following steps: S1. Preparation of electrolyte: Deionized water was heated to 51°C, and copper sulfate pentahydrate (310 g / L), sulfuric acid (105 g / L), and hydrochloric acid (46.28 mg / L) were added sequentially. After stirring until all materials were fully dissolved, polyethylene glycol (PEG) (20 mg / L), sodium 3-mercapto-1-propanesulfonate (MPS) (1.5 mg / L), polypropylene glycol (PPG) (12 mg / L), and sodium dodecyl sulfate (SDS) (2.5 mg / L) were added sequentially. The mixture was stirred evenly to obtain the electrolyte. S2. Preparation of ultra-thick copper foil: Titanium / stainless steel is used as the cathode roller, and an iridium-coated titanium plate is used as the anode. The distance between the cathode and anode is 25 mm. The electrolyte is transported by overflow circulation from a high-level tank, and the current density is controlled at 16 A / dm³. 2Electrolytic deposition is carried out at a raw foil line speed of 1.5 m / min. The electrolytically formed copper foil immediately enters the online water washing and drying process. After being sprayed with room temperature pure water for 5 seconds and dried, it is wound up with a winding tension of 170 kg to obtain an ultra-thick copper foil with a thickness of 105 μm. Example 2

[0026] The process is basically the same as in Example 1, except that the concentrations of the components in the electrolyte are different. Specifically, it includes the following steps: S1. Preparation of electrolyte: Deionized water was heated to 51°C, and copper sulfate pentahydrate (310 g / L), sulfuric acid (105 g / L), and hydrochloric acid (46.28 mg / L) were added sequentially. After stirring until all materials were fully dissolved, polyethylene glycol (PEG) (15 mg / L), sodium 3-mercapto-1-propanesulfonate (MPS) (1.0 mg / L), polypropylene glycol (PPG) (17 mg / L), and sodium dodecyl sulfate (SDS) (1.5 mg / L) were added sequentially. The mixture was stirred evenly to obtain the electrolyte. S2. Preparation of ultra-thick copper foil: Titanium / stainless steel is used as the cathode roller, and an iridium-coated titanium plate is used as the anode. The distance between the cathode and anode is 25 mm. The electrolyte is transported by overflow circulation from a high-level tank, and the current density is controlled at 16 A / dm³. 2 Electrolytic deposition is carried out at a raw foil line speed of 1.5 m / min. The electrolytically formed copper foil immediately enters the online water washing and drying process. After being sprayed with room temperature pure water for 5 seconds and dried, it is wound up with a winding tension of 170 kg to obtain an ultra-thick copper foil with a thickness of 105 μm. Example 3

[0027] The process is basically the same as in Example 1, except that the concentrations of the components in the electrolyte are different. Specifically, it includes the following steps: S1. Preparation of electrolyte: Deionized water is heated to 51°C, and copper sulfate pentahydrate (310 g / L), sulfuric acid (105 g / L), and hydrochloric acid (46.28 mg / L) are added sequentially. After stirring until all materials are fully dissolved, polyethylene glycol (PEG) (28 mg / L), sodium 3-mercapto-1-propanesulfonate (MPS) (3.0 mg / L), polypropylene glycol (PPG) (10 mg / L), and sodium dodecyl sulfate (SDS) (3 mg / L) are added sequentially. The mixture is stirred evenly to obtain the electrolyte. S2. Preparation of ultra-thick copper foil: Titanium / stainless steel is used as the cathode roller, and an iridium-coated titanium plate is used as the anode. The distance between the cathode and anode is 25 mm. The electrolyte is transported by overflow circulation from a high-level tank, and the current density is controlled at 16 A / dm³. 2Electrolytic deposition is carried out at a raw foil line speed of 1.5 m / min. The electrolytically formed copper foil immediately enters the online water washing and drying process. After being sprayed with room temperature pure water for 5 seconds and dried, it is wound up with a winding tension of 170 kg to obtain an ultra-thick copper foil with a thickness of 105 μm. Comparative Example 1

[0028] The process is basically the same as in Example 1, except that PEG, MPS, PPG, and SDS are not added to the electrolyte. The specific steps include: S1. Preparation of electrolyte: Heat deionized water to 51°C, and add copper sulfate pentahydrate (310 g / L), sulfuric acid (105 g / L), and hydrochloric acid (46.28 mg / L) to it in sequence. Stir until all materials are fully dissolved to obtain the electrolyte. S2. Preparation of ultra-thick copper foil: Titanium / stainless steel is used as the cathode roller, and an iridium-coated titanium plate is used as the anode. The distance between the cathode and anode is 25 mm. The electrolyte is transported by overflow circulation from a high-level tank, and the current density is controlled at 16 A / dm³. 2 Electrolytic deposition is carried out at a raw foil line speed of 1.5 m / min. The electrolytically formed copper foil immediately enters the online water washing and drying process. After being sprayed with room temperature pure water for 5 seconds and dried, it is wound up with a winding tension of 170 kg to obtain ultra-thick copper foil. Test Example 1

[0029] The ultrathick copper foils prepared in Example 1 and Comparative Example 1 were characterized by scanning electron microscopy, and the results are as follows: Figures 1-2 As shown. From Figures 1-2 As can be seen, the ultra-thick copper foil of Comparative Example 1 has a large number of coarse, prominently protruding large hemispherical and dendritic copper nodules on its surface. The copper nodules are densely distributed, corresponding to a large number of black spot defects observed visually. The roughness of the original surface of the copper foil is seriously excessive. In contrast, the ultra-thick copper foil of Example 1 has almost no large copper nodules in its microscopic field of view. The surface of the copper foil is uniformly and smoothly crystallized, without obvious protruding coarse grain defects. Visually, the copper foil is clean and free of black spots. This indicates that the compound additive system can inhibit the abnormal dendritic growth of copper ions from the source during the electrolytic deposition stage, completely avoid the problem of large copper nodule precipitation, and significantly optimize the smoothness of the original surface of the ultra-thick raw foil. Test Example 2

[0030] The ultra-thick copper foils prepared in Examples 1-3 and Comparative Example 1 were tested: (1) Surface roughness: Using a roughness profiler, the test area was selected on the rough surface of the copper foil according to the ISO 4287 standard. The maximum peak height and maximum valley depth of 5 sets of profiles were measured and the corresponding maximum profile height was calculated, i.e., surface roughness. (2) Copper nodule height: The vertical height from the base of the copper nodule particles to the top of the protrusion was measured by scanning electron microscopy. (3) Copper nodule density: The number of copper nodule particles with a diameter exceeding the limit standard per unit area is counted by measuring the rough surface of the copper foil using an optical microscope, which is the copper nodule density. (4) Tensile strength: Cut the copper foil into strips of 200mm×13mm and use a universal testing machine to stretch the sample at a tensile rate of 50mm / min until it breaks. Record the maximum stress value during the fracture process of the sample, which is the tensile strength. (5) Elongation: In a tensile test, the percentage increase in gauge length after the specimen breaks relative to the initial gauge length is called elongation. Figures 3-6 Table 1 shows the final measured parameters: Table 1

[0031] from Figures 3-6 As shown in Table 1, the copper foils prepared in each embodiment have a dense and regular grain arrangement, with only a few minor protrusions on the surface and no large, tall, or coarse copper nodules. In contrast, the copper foil prepared in Comparative Example 1 clearly shows a large number of dendrites and hemispherical protrusions with significant height differences, resulting in severe surface unevenness and prominent primary defects. Quantitative test data show that the copper foils prepared in the embodiments have low surface roughness, the height of copper nodules is controlled within the target range, and the overall amount of copper nodules generated per unit area is low. At the same time, the tensile strength and elongation of the copper foils prepared in the embodiments exceed the set minimum indicators, and the weight values ​​fluctuate little. The thickness of the copper foil is stably maintained in the ultra-thick specification range, and the thickness uniformity is good.

[0032] In summary, this demonstrates that a specific ratio of multi-component composite additives, combined with appropriate electrolytic process parameters, can suppress abnormal dendrite precipitation of copper ions during the electrocrystallization stage, effectively improve the surface smoothness of ultra-thick copper foil, reduce the size and density of copper nodules, and stably impart excellent tensile mechanical properties to the copper foil. This solves the industry pain points of traditional ultra-thick copper foil electrolytic foil production processes, such as frequent copper nodules, high surface roughness, and substandard mechanical properties.

[0033] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A process for electrolytically producing ultra-thick copper foil with low copper nodules and low roughness, characterized in that, Includes the following steps: S1. Add copper source, sulfuric acid, chlorine source, leveling agent, brightener, inhibitor and surfactant to water and stir evenly to obtain electrolyte; S2. Immerse the cathode roller and anode in the electroplating solution for electrolytic deposition to obtain the ultra-thick copper foil with low copper nodules and low roughness.

2. The electrolytic foil production process for ultra-thick copper foil with low copper nodules and low roughness according to claim 1, characterized in that, In S1, the temperature of the water is 48℃-54℃.

3. The electrolytic foil production process for ultra-thick copper foil with low copper nodules and low roughness according to claim 1, characterized in that, In S1, the copper source is copper sulfate; And / or, the chlorine source is selected from hydrochloric acid and / or sodium chloride; And / or, the leveling agent is polyethylene glycol; And / or, the brightener is sodium 3-mercapto-1-propanesulfonate; And / or, the inhibitor is polypropylene glycol; And / or, the surfactant is selected from sodium dodecyl sulfate and / or hexadecyltrimethylammonium bromide.

4. The electrolytic foil production process for ultra-thick copper foil with low copper nodules and low roughness according to claim 1, characterized in that, In S1, the concentration of the copper source in the electrolyte is 290 g / L-310 g / L, the concentration of sulfuric acid is 90 g / L-120 g / L, the concentration of the chlorine source is 30 mg / L-60 mg / L, the concentration of the leveling agent is 13 mg / L-30 mg / L, the concentration of the brightener is 1.0 mg / L-3.0 mg / L, the concentration of the inhibitor is 7 mg / L-20 mg / L, and the concentration of the surfactant is 1.0 mg / L-3.5 mg / L.

5. The electrolytic foil production process for ultra-thick copper foil with low copper nodules and low roughness according to claim 1, characterized in that, In S2, the cathode roller is made of titanium / stainless steel.

6. The electrolytic foil production process for ultra-thick copper foil with low copper nodules and low roughness according to claim 1, characterized in that, In S2, the surface roughness of the cathode roller does not exceed 2 μm.

7. The electrolytic foil production process for ultra-thick copper foil with low copper nodules and low roughness according to claim 1, characterized in that, In S2, the anode material is an iridium-coated titanium plate.

8. The electrolytic foil production process for ultra-thick copper foil with low copper nodules and low roughness according to claim 1, characterized in that, In S2, during the electrolytic deposition process, the distance between the cathode roller and the anode is 20mm-30mm.

9. The electrolytic foil production process for ultra-thick copper foil with low copper nodules and low roughness according to claim 1, characterized in that, In S2, the current density of the electrolytic deposition is 12 A / dm³. 2 -18A / dm 2 The foil production line speed is 1m / min-2m / min.

10. The electrolytic foil production process for ultra-thick copper foil with low copper nodules and low roughness according to claim 1, characterized in that, In S2, the ultra-thick copper foil with low copper nodules and low roughness has a thickness of 100μm-210μm, a surface roughness of ≤1.7μm, a copper nodule height of ≤1.6μm, a tensile strength of ≥350MPa, and an elongation of ≥20%.